PENGARUH KINERJA KEUANGAN DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Basic Industry dan Chemicals yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019) - Maulia Mustafani; Chasan Azari; Setya Prihatiningtyas (Faculty of Social and Political Science, 2021)
The company value is the expectation of stakeholders. If it has good value, the stakeholders will have good welfare. There are two factors that affect the company value, namely external and internal factors. This study indicates the company value as dependent variable which is measured using price book value. This measurement compares stock price with the book value. The independent variables are financial performance and intellectual capital. Financial performance is measured using the current ratio, dept to equity ratio, and return on equity ratio. Whereas, intellectual capital uses the measurement of value-added intellectual coefficient (VAIC). The purpose of the study is to determine and examine the effect of financial performance and intellectual capital on the company value in basic and chemical industries listed on the Indonesia Stock Exchange (BEI) from 2017 to 2019. There are twenty-seven basic and chemical industries that have been selected using a census method. The data using descriptive statistical analysis, classical assumption test, multiple linear regression test, and hypothesis. The result of the study indicates financial performance and intellectual capital simultaneously affect the company value. However, financial performance which is measured using CR and ROE, shows significant negative effect on the company value. Furthermore, financial performance which is measured using ROE, has significant positive effect on the company value. The result also indicates that intellectual capital has negative effect on the company value.